Efficacy of different amendments and residual effects on nickel toxicity and nutritional quality in wheat/rice continuous system and health risk assessment in Ultisol. Issue 13 (10th November 2023) - Ali, Umeed; Abdelrhman, Fatma; Bashir, Saqib; Shaaban, Muhammad; Shah, Zia-Ul-Hassan; Rady, Omar; Fu, Qingling; Zhu, Jun; Hu, Hongqing
ABSTRACT: Rice straw (RS), biochar (BC) and lime (LM) have proved to be effective immobilizing agents in acidic contaminated soil. Up-to-date scientific data is lacking regarding residual effects of these amendments in acidic soils and wheat/rice cropping system. The objective was to analyze the efficacy of amendments to improve grain yields, nutritional quality, and reduce Ni bioavailability of wheat/rice rotation system. A pot experiment was conducted to examine the efficacy of RS, BC 10 and 20 g kg −1 and LM 10 g kg −1 application rates on plant growth, nutritional quality and Ni contents in wheat and rice tissues and grain. Amendments enhanced Ni immobilization, declined their uptake by plants and accumulation in the grains of both crops. Rice straw biochar reduced several factors like health risk assessment, Ni uptake and bioconcentration factor. BC 20 g kg −1 increased shoot, root and grain yields, while enhanced essential nutrients in the wheat/rice cropping system compared to untreated soil. Soil amendments significantly decreased toxicity characteristics leaching procedure (TCLP) extractable Ni by 42.25% and 42.62% and simple bioaccessibility extraction test (SBET) by 42.1% and 45.25% in post- wheat/rice crops. This process enhanced the safety of wheat/rice rotation cropping system to be consumed and mitigated security risks.